Integrated survey procedures for seismic protection of monumental liturgical furniture. Issue 1 (1st April 2022) - Trizio, I; Savini, F; Marra, A; Fabbrocino, G
Abstract: The research herein reported deals with the digital survey potential in the knowledge and documentation of particular sculptural artefacts located in medieval churches, such as pulpits, candelabra and ciboria, with careful attention to the issues related to modelling for structural analysis of these artefacts. In particular, the pulpit's typology has been analysed; it is a piece of liturgical furniture that has its own response to external stresses, although it is not a structural element. An operational procedure was defined through the discussion of a real case located in the L'Aquila territory. The procedure starts from the knowledge phase of the artefacts enabling the implementation of a digital model by integrating the data of terrestrial photogrammetry and laser scanner. The results achieved highlight the advantages of using detailed digital models for cognitive analysis but also the open issues in the context of model optimisation for specific analyses, such as structural ones, required within integrated approaches for heritage protection and conservation.